Dėl lie. kúopa ir kaũpas etimologinio siejimo - Karaliūnas, Simas (Baltistica, 1969)
ON THE ETYMOLOGICAL IDENTIFICATION OF LITH. kúopa AND kaũpasThe paper deals with an etymological analysis of Lith. kúopa “crowd, throng, multitude; heap, pile etc.”, Latv. kuõpa “heap, pile; crowd etc.” and Lith. kaũpas “heap, pile”, which are supposed to stem from one and the same root. A thorough examination of these examples shows that they most likely belong to quite different roots from the etymological point of view, thus there is no basis to assume an apophony uo : au in Baltic. The vocalism uo of Lith. kúopa, Latv. kuõpa derived from Baltic ō represents e / o apophonic series. Lith. kúopa, Latv. kuõpa may be etymologically identified with the verbs Lith. kuõpti “clean; harvest, gather in; snatch, seize, grasp, grab, plunder”, Latv. kùopt “clean; apply, wait etc.”. The last two are the morphonological continuants of the Baltic root *kep- (or *kap-) “take, snatch, seize, grasp” represented by Lith. kė̃pti, Latv. ķept, ķêpît, Lith. kàptelėti, kàpterti, kàpalioti, kapaliúoti, kópti. The vocalism au of Lith. kaũpas belongs to и apophonic series. Lith. kaũpas, OPr. Caupe- (in the river name Caupeaps) may be etymologically identified with the verb kaũpti “hill, earth up, hoe” (which in all probability is a denominative) and derived from the Baltic root *keu-p- / *ku-p- “bend, turn out(wards), become convex (while growing sour, thriving, getting in heap)” which is represented in Lith. kùpti, kupė́ti, Latv. kupt, kupêt, Lith. prisi-kiaupti, Latv. ķaũpêtiês.